1992
DOI: 10.1097/00001888-199204000-00019
|View full text |Cite
|
Sign up to set email alerts
|

A tutorial for students demonstrating adequate skills but inadequate knowledge after completing a medicine clerkship at the Oregon Health Sciences University

Abstract: Upon completing a clinical clerkship, some students demonstrate adequate clinical skills appropriate for that clerkship but do not demonstrate an adequate fund of knowledge or ability to apply their knowledge clinically. For such students, repeating all or a portion of the clerkship may not be appropriate. This study describes a tutorial provided such students after they had completed the medicine clerkship at the Oregon Health Sciences University. During a two-year period (academic years 1988-89 and 1989-90),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…These findings are at odds with those of a number of studies that have evaluated performance on written or clinical examinations before and after a specific remediation intervention 7,14–38 and concluded that the intervention was effective. However, single studies ‘are limited in the generalisability of the knowledge they produce about concepts, populations, settings and times’ and ‘frequently illuminate only one part of a larger explanatory puzzle’ 39 .…”
Section: Introductionmentioning
confidence: 66%
“…These findings are at odds with those of a number of studies that have evaluated performance on written or clinical examinations before and after a specific remediation intervention 7,14–38 and concluded that the intervention was effective. However, single studies ‘are limited in the generalisability of the knowledge they produce about concepts, populations, settings and times’ and ‘frequently illuminate only one part of a larger explanatory puzzle’ 39 .…”
Section: Introductionmentioning
confidence: 66%
“…Successful remediation plans for students who fail the National Board of Medical Examiners internal medicine subject exam include self-directed study, 7 faculty-led tutorials with directed reading, attendance at teaching conferences, and problem-based discussion sessions. 27 Successful remediation of inadequate clinical performance has been demonstrated for students failing a Clinical Performance Examination. 9 Lin et al 28 published a case report of the successful remediation of a student with communication skills deficiencies.…”
Section: Remediation Plansmentioning
confidence: 99%
“…Failing students manifest problems in either cognitive skills (history-taking, physical examination, clinical knowledge, and clinical reasoning), noncognitive skills (professionalism and communication), or both. 12 Although small, singleinstitution studies have reported strategies designed to remediate deficits in the cognitive and noncognitive domains, [13][14][15][16][17] approaches to remediation vary widely. [13][14][15][16][17][18] To our knowledge, no studies identify optimal remediation strategies, nor are there guidelines regarding how to remediate a particular skill deficit.…”
Section: Resultsmentioning
confidence: 99%
“…Organized group activities have already been shown to be successful in remediating clinical knowledge and reasoning deficits after core clerkships. 15 Organized group activities may better address clinical reasoning deficits because they provide students with immediate feedback and the opportunity to build on experience by actively applying knowledge, both of which are important in developing clinical reasoning skills. 35,41,42 Organized group activities allow failing students to observe and interact with similarly performing peers, a process that promotes reflection on personal strengths and weaknesses.…”
Section: Discussionmentioning
confidence: 99%